2003
DOI: 10.1111/j.1349-7006.2003.tb01356.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carvedilol on MDR1 ‐mediated multidrug resistance: comparison with verapamil

Abstract: ultidrug resistance (MDR) is one of the most serious problems responsible for the failure of chemotherapy, and cellular factors associated with MDR include: 1) down-regulation of uptake or induction of the efflux system (e.g. MDR1 (P-glycoprotein)); 2) induction of inactivation enzymes including GSH-S-tranferase; 3) alteration of targeted enzymes including topoisomerase; 4) changes in DNA repair processes; and 5) alteration of apoptotic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 27 publications
0
22
2
2
Order By: Relevance
“…Thus, it is expected that MDR1 plays an important role in the pharmacokinetics of various types of structurally unrelated drugs. In addition, it has been demonstrated that MDR1 has been found to be a key protein for drug interaction, similarly to CYPs [59][60][61][62].…”
Section: What Is Mdr1?mentioning
confidence: 97%
“…Thus, it is expected that MDR1 plays an important role in the pharmacokinetics of various types of structurally unrelated drugs. In addition, it has been demonstrated that MDR1 has been found to be a key protein for drug interaction, similarly to CYPs [59][60][61][62].…”
Section: What Is Mdr1?mentioning
confidence: 97%
“…• Inhibition of CYP 2D6 by nilotinib: 1 metoprolol exposure 9,18,19 Bisoprolol • Inhibition of CYP 2D6 by imatinib: 1 bisoprolol exposure 18 • Inhibition of CYP 3A4 by dasatinib: 1 bisoprolol exposure 9,18 • Inhibition of CYP 2D6 by nilotinib: 1 bisoprolol exposure 9,18,19 Carvedilol • Inhibition of CYP 2C9 and 2D6 by imatinib: 1 carvedilol exposure 18 • Inhibition of Pgp by carvedilol: 1 imatinib exposure 64,71,77 • Inhibition of Pgp by carvedilol: 1 dasatinib exposure 9,10,52,67,68,77…”
Section: Hmg-coa Reductase Inhibitorsmentioning
confidence: 99%
“…9 However, it has been demonstrated before that propranolol, metoprolol, and atenolol did not affect P-gp transport, 10 suggesting that the effects of carvedilol are independent of its actions on ␤-adrenoceptors. This was confirmed with our findings utilizing blood pressure and heart rate changes.…”
Section: Potential Mechanism Of Csa-carvedilol Interactionmentioning
confidence: 97%
“…However, recent reports have suggested that carvedilol, but not metoprolol, modulates P-glycoprotein (P-gp), a membrane protein that regulates CsA absorption. 9,10 The primary objective of this study was to compare the effects of carvedilol and metoprolol on CsA trough levels when initiated in cardiac transplant recipients.…”
mentioning
confidence: 99%